Impact of quantity of anhydrite, water to binder ratio, fineness on kinetics and phase assemblage of belite-ye'elimite-ferrite cement. (September 2017) - Morin, Vincent; Termkhajornkit, Pipat; Huet, Bruno; Pham, Gerard
Abstract: One of the main challenge in belite, ye'elimite and ferrite cement is the control of the belite phase reactivity. We propose to study two mechanisms that impact belite hydration kinetic: the first mechanism is linked to available space for hydration products and can be seen as a decrease of water accessibility to cement surface and the second concerns the cement fineness. We used a thermodynamic model that can predict phase assemblage and we found good correlations between this model and the results obtained with XRD measurement and Rietveld refinement.